The importance of reactive silica for maintaining soil health - Jörg Schaller; Markus Kleber; Daniel Puppe; Mathias Stein; Michael Sommer; Matthias C. Rillig (Plant and Soil, 2025)
Background and aim Soil health is vital for the sustainability of ecosystem services such as food and fiber production, nutrient cycling and water supply. Soil health can be assessed through a combination of physical, biological and chemical metrics. There is emerging evidence that reactive silica is a strong factor controlling soil functions. Scope We explain how reactive silica, specifically dissolved silicic acid and amorphous silica, can be used as a new metric for assessing soil health, complementing traditional metrics or even substituting for them. Conclusion The pivotal role of reactive silica for soil health is particularly important under stress conditions that are typically associated with drought and soil degradation. The status of reactive silica indicates soil degradation earlier than the currently used metrics, because reactive silica depletion is followed by soil degradation. We recommend suitable methods and benchmarks for assessing reactive silica. Furthermore, we suggest further research to improve our understanding of the importance of reactive silica for soil health. We call upon the soil research community to include reactive silica as a metric for soil health assessment.